113 Theatre Bleep: Quality Improvement Project. (4th May 2021) - Weale, R; Rivers, C
Abstract: Introduction: Efficient use of any theatre is essential for timely operating and maximising the use of resources. There are many reasons for inefficiency, including delays in patient transfer, and issues of communication between the ward and theatre staff. The objectives of this QIP were to establish areas for improvement in communication. Method: A survey was distributed amongst staff with several questions subjectively rating the communication between theatres and the ward. Results: Common reasons listed for delays mentioned included staffing (25) and communication (19), with only 18% rating communication when sending for a patient as good, and 58% of theatre staff rating communication when transporting a patient back as poor. A common response was failure of the ward to answer the telephone. A bleep was therefore introduced, which was carried by a nominated nurse on the plastic surgery ward each shift. Following the introduction of this bleep, the survey was repeated, with 71% rating communication when sending for a patient as good, and 86% of staff rating communication when transporting a patient back as either good or excellent. Conclusions: This simple measure of a new ward bleep significantly improved communication, and we feel this measure should be implemented nationally.